2019
DOI: 10.1101/546952
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CXCR3-expressing metastasis-initiating cells induce and exploit a fibroblast niche in the lungs to fuel metastatic colonization

Abstract: Metastatic colonization relies on interactions between disseminated cancer cells and the microenvironment in secondary organs. Here, we show that disseminated breast cancer cells evoke major phenotypic changes in lung fibroblasts to form a metastatic niche that supports malignant growth. Colonization of the lungs by cancer cells confers an inflammatory phenotype in associated fibroblasts, where IL-1α and IL-1β, secreted by breast cancer cells, induce CXCL9 and CXCL10 production in metastasis-associated fibrobl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
(70 reference statements)
0
2
0
Order By: Relevance
“…It functions through binding to the receptor CXCR3, which has two different isoforms of CXCR3A and CXCR3B (Ma et al 2015). Recent studies have demonstrated newfound roles in T cell activation and proliferation (Tan et al 2018; Gao et al 2020), angiogenesis (Ding et al 2016; Shen et al 2019), and fibroblast activation (Pein et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It functions through binding to the receptor CXCR3, which has two different isoforms of CXCR3A and CXCR3B (Ma et al 2015). Recent studies have demonstrated newfound roles in T cell activation and proliferation (Tan et al 2018; Gao et al 2020), angiogenesis (Ding et al 2016; Shen et al 2019), and fibroblast activation (Pein et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Pein et al use a murine model of BC to demonstrate that JNK signaling from cancer cells induces IL1α, and IL1ß expression, which binds to IL1R in stromal fibroblasts, activating NFKß signaling and increasing fibroblast expression of CXCL9 and CCXL10 that feeds forward to bind to CCR3 on cancer cells. This generates a feedback loop that leads to a pro‐metastatic environment (Pein et al 2019).…”
Section: Introductionmentioning
confidence: 99%